2023
DOI: 10.3390/vaccines11081391
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Adjuvanted Influenza Vaccines

Shintaro Shichinohe,
Tokiko Watanabe

Abstract: The numerous influenza infections that occur every year present a major public health problem. Influenza vaccines are important for the prevention of the disease; however, their effectiveness against infection can be suboptimal. Particularly in the elderly, immune induction can be insufficient, and the vaccine efficacy against infection is usually lower than that in young adults. Vaccine efficacy can be improved by the addition of adjuvants, and an influenza vaccine with an oil-in-water adjuvant MF59, FLUAD, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Ever since then, MF59 platform has been advanced to make Fluad quadrivalent vaccine against influenza virus subtypes A (H1N1, H3N2) and B (Yamagata, Victoria), Audenz™ against an influenza A of H5N1, as well as Focetria against 2009 H1N1 influenza A pandemic. [20] Noteworthy, a recent systematic review on sources from electronic databases and grey literature up to February 7, 2020 showed that, in terms of vaccine effectiveness (VE), MF59 adjuvanted trivalent influenza vaccines were effective in preventing laboratory-confirmed influenza in older adults (aged ≥65 years). [18] However, the review also showed that in terms of relative VE, there was no significant difference between the MF59 adjuvanted trivalent influenza vaccines and non-adjuvanted vaccines of either trivalent one or quadrivalent one.…”
Section: The Translational Platforms For the Inactivated Vaccines Pot...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ever since then, MF59 platform has been advanced to make Fluad quadrivalent vaccine against influenza virus subtypes A (H1N1, H3N2) and B (Yamagata, Victoria), Audenz™ against an influenza A of H5N1, as well as Focetria against 2009 H1N1 influenza A pandemic. [20] Noteworthy, a recent systematic review on sources from electronic databases and grey literature up to February 7, 2020 showed that, in terms of vaccine effectiveness (VE), MF59 adjuvanted trivalent influenza vaccines were effective in preventing laboratory-confirmed influenza in older adults (aged ≥65 years). [18] However, the review also showed that in terms of relative VE, there was no significant difference between the MF59 adjuvanted trivalent influenza vaccines and non-adjuvanted vaccines of either trivalent one or quadrivalent one.…”
Section: The Translational Platforms For the Inactivated Vaccines Pot...mentioning
confidence: 99%
“…Ever since then, MF59 platform has been advanced to make Fluad quadrivalent vaccine against influenza virus subtypes A (H1N1, H3N2) and B (Yamagata, Victoria), Audenz™ against an influenza A of H5N1, as well as Focetria against 2009 H1N1 influenza A pandemic. [ 20 ]…”
Section: The Whole Microbe‐based Vaccines and Translational Platformsmentioning
confidence: 99%
“…Adjuvant systems 03 (AS03) and emulsions of oil in water MF59 have been used as adjuvants in pandemic monovalent influenza vaccinations and seasonal adjuvanted trivalent influenza vaccines (ATIVs) [56,57]. AS03 is an emulsion of oil and water that includes polysorbate 80, DL-α-tocopherol, and squalene [56,58]. It has been used in the development of pandemic influenza vaccines and enhanced the immune response [56].…”
Section: Immunogenicity and Safety Of Different Types Of Influenza Va...mentioning
confidence: 99%
“…It has been used in the development of pandemic influenza vaccines and enhanced the immune response [56]. Aqua-oil emulsion is another adjuvant that has been utilized in pandemic monovalent and seasonal ATIVs, which is MF59 [56,58]. Squalene, polysorbate 80, and sorbitan trioleate make up its composition [56].…”
Section: Immunogenicity and Safety Of Different Types Of Influenza Va...mentioning
confidence: 99%
See 1 more Smart Citation